2020
DOI: 10.1074/jbc.ra120.015661
|View full text |Cite
|
Sign up to set email alerts
|

Murine GFP-Mx1 forms nuclear condensates and associates with cytoplasmic intermediate filaments: Novel antiviral activity against VSV

Abstract: Type I and III interferons (IFNs) induce expression of the “myxovirus resistance proteins” MxA in human cells and its ortholog Mx1 in murine cells. Human MxA forms cytoplasmic structures, while murine Mx1 forms nuclear bodies. While both HuMxA and MuMx1 are antiviral towards influenza A virus (FLUAV) (an orthomyxovirus), only HuMxA is considered antiviral towards vesicular stomatitis virus (VSV) (a rhabdovirus). We previously reported that the cytoplasmic human GFP-MxA structures were phase-separated membranel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 71 publications
1
43
0
Order By: Relevance
“…All cultures were then immunostained for MxA. Panel C, IFN-α2-treated cultures (10 ng/ml, 2 days) were infected with VSV (moi >10 pfu/cell) (44, 46) for 5 hr, fixed and immunostained for MxA (green) and for VSV N (red). Arrows: cells showing condensates with both MxA and VSV N protein.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All cultures were then immunostained for MxA. Panel C, IFN-α2-treated cultures (10 ng/ml, 2 days) were infected with VSV (moi >10 pfu/cell) (44, 46) for 5 hr, fixed and immunostained for MxA (green) and for VSV N (red). Arrows: cells showing condensates with both MxA and VSV N protein.…”
Section: Resultsmentioning
confidence: 99%
“…Cultures were fizxed in 4% PFA in isotonic PBS or one-third strength PBS (1 hr at 4 o C immunostained for VSV nucleocapsid (N) protein using an mAb provided by Dr. Douglas S. Lyles (mAb 10G4). N-protein immunofluorescence (in red) in GFP-positive (nuclear or cytoplasmic) and negative cells was quantitated on a per cell basis as summarized in Davis et al (44) and Sehgal et al (46) and expressed in arbitrary units (AU) as integrated intensity/cell.…”
Section: Vsv Stock and Virus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…MLOs regulate diverse cellular function, such as protein turnover, mitosis mRNA storage and translation, virus replication, and antiviral activity. Murine Mx1 and Mx2 were observed in nuclear bodies and granular cytoplasmic structures [ 73 ]. Coincidentally, exogenously expressed as well as IFN induced human MxA protein also forms as membrane-less condensates in the cytoplasm, and interacts with and sequesters viral nucleocapsid proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Stubbe and colleagues demonstrated that PML bodies were enriched around viral replication centers when viral DNA binding proteins were modified with SUMOs, thereby mediating the replication of the virus ( 50 ). In addition, Sehgal revealed that the murine cognate Mx1 could form nuclear condensates overlapping with PML nuclear bodies, further exerting a vital antiviral activity ( 51 ).…”
Section: Several Membraneless-organelles and Associated Functions In Cellsmentioning
confidence: 99%